Antineonatal Fc Receptor Antibody Treatment Ameliorates MOG-IgG–Associated Experimental Autoimmune Encephalomyelitis. Issue 2 (March 2022) - Remlinger, Jana; Madarasz, Adrian; Guse, Kirsten; Hoepner, Robert; Bagnoud, Maud; Meli, Ivo; Feil, Moritz; Abegg, Mathias; Linington, Christopher; Shock, Anthony; Boroojerdi, Babak; Kiessling, Peter; et al.
Abstract : Background and Objectives: Myelin oligodendrocyte glycoprotein antibody–associated disorder (MOGAD) is a rare, autoimmune demyelinating CNS disorder, distinct from multiple sclerosis and neuromyelitis optica spectrum disorder. Characterized by pathogenic immunoglobulin G (IgG) antibodies against MOG, a potential treatment strategy for MOGAD is to reduce circulating IgG levels, e.g., by interference with the IgG recycling pathway mediated by the neonatal Fc receptor (FcRn). Although the optic nerve is often detrimentally involved in MOGAD, the effect of FcRn blockade on the visual pathway has not been assessed. Our objective was to investigate effects of a monoclonal anti-FcRn antibody in murine MOG-IgG–associated experimental autoimmune encephalomyelitis (EAE). Methods: We induced active MOG35-55 EAE in C57Bl/6 mice followed by the application of a monoclonal MOG-IgG (8-18C5) 10 days postimmunization (dpi). Animals were treated with either a specific monoclonal antibody against FcRn (α-FcRn, 4470) or an isotype-matched control IgG on 7, 10, and 13 dpi. Neurologic disability was scored daily on a 10-point scale. Visual acuity was assessed by optomotor reflex. Histopathologic hallmarks of disease were assessed in the spinal cord, optic nerve, and retina. Immune cell infiltration was visualized by immunohistochemistry, demyelination by Luxol fast blue staining and complement deposition and number of retinal ganglion cells by immunofluorescence. Results: In MOG-IgG–augmented MOG35-55 EAE, anti-FcRn treatment significantly attenuated neurologic disability over the course of disease (mean area under the curve and 95% confidence intervals (CIs): α-FcRn [n = 27], 46.02 [37.89–54.15]; isotype IgG [n = 24], 66.75 [59.54–73.96], 3 independent experiments), correlating with reduced amounts of demyelination and macrophage infiltration into the spinal cord. T- and B-cell infiltration and complement deposition remained unchanged. Compared with isotype, anti-FcRn treatment prevented reduction of visual acuity over the course of disease (median cycles/degree and interquartile range: α-FcRn [n = 16], 0.50 [0.48–0.55] to 0.50 [0.48–0.58]; isotype IgG [n = 17], 0.50 [0.49–0.54] to 0.45 [0.39–0.51]). Discussion: We show preserved optomotor response and ameliorated course of disease after anti-FcRn treatment in an experimental model using a monoclonal MOG-IgG to mimic MOGAD. Selectively targeting FcRn might represent a promising therapeutic approach in MOGAD.